Nanosecond laser thermal reconfiguration fish scale zinc negative electrode and preparation method and application thereof

CN122950366APending Publication Date: 2026-10-20TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611441680.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0007]本发明为了解决现有技术中锌负极界面调控主要依赖烧蚀作用,但规则结构的边缘易引入新的电场集中点,且过高激光能量易导致锌箔表面过度烧蚀、颗粒堆积、裂纹形成以及基底损伤,导致电极长期稳定性不足的问题,提供了一种纳秒激光热重构鱼鳞状锌负极及其制备方法与应用

Benefits of technology

本发明提供的一种纳秒激光热重构鱼鳞状锌负极及其制备方法与应用,利用纳秒激光对锌金属基底进行表面扫描加工,通过局部热作用使锌基底表面依次发生局部升温、熔融、表面物质迁移和快速凝固,构筑具有连续弧形搭接的鱼鳞状热重构结构,鱼鳞状热重构结构具有圆滑边缘和连续空间分布特征,可减少尖锐结构引起的局部电场集中,从而改善锌负极界面结构均匀性及锌沉积/剥离行为。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of battery material preparation technology, and discloses a nanosecond laser thermally reconstructed fish-scale-shaped zinc anode, its preparation method, and its application. The preparation process includes first cutting, flattening, cleaning, and drying a zinc metal substrate, then fixing it flat on a nanosecond laser processing platform. A nanosecond pulsed laser is used to scan and process the surface of the zinc metal substrate, causing localized heating, melting, surface material migration, and rapid solidification, forming a fish-scale-shaped thermally reconstructed structure. Finally, the zinc anode is obtained after cooling, cleaning, and cutting. This invention utilizes nanosecond laser-induced self-thermal reconstructing of the zinc substrate to form a fish-scale-shaped microstructure with smooth edges and continuous distribution, which can effectively improve zinc deposition / stripping behavior, enhance the interface stability and cycle life of the zinc anode, and is suitable for aqueous zinc-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery material preparation technology, and particularly relates to the field of zinc metal anode surface processing, specifically a nanosecond laser thermal reconstructed fish-scale zinc anode and its preparation method and application. Background Technology

[0002] Aqueous zinc-ion batteries possess advantages such as high safety, low cost, environmental friendliness, and abundant zinc resources, making them promising for applications in large-scale energy storage, grid peak shaving, and flexible energy storage. Zinc metal anodes, with their high theoretical capacity, low redox potential, and good compatibility with aqueous electrolytes, are commonly used anode materials in aqueous zinc-ion batteries.

[0003] However, during long-term charge-discharge processes, zinc anodes commonly exhibit interfacial instability in aqueous electrolytes. Commercial zinc foil surfaces typically contain non-uniform regions such as rolling textures, micro-scratches, grain boundaries, localized protrusions, and processing defects. These defects can easily lead to localized electric field concentration and Zn... 2+ Uneven ion flux distribution causes zinc ions to preferentially deposit in highly active regions, inducing uneven zinc deposition and even dendrite growth. Simultaneously, issues such as hydrogen evolution reaction, zinc corrosion, and accumulation of insulating byproducts in aqueous electrolytes further damage the zinc anode / electrolyte interface, leading to increased battery polarization, reduced coulombic efficiency, and decreased cycle life. In severe cases, this can even cause separator damage and internal short circuits. Therefore, developing novel zinc anode materials with stable interface structures and uniform zinc deposition capabilities is of great significance for improving the performance of aqueous zinc-ion batteries.

[0004] To address the aforementioned issues, various strategies for controlling the zinc anode interface have been proposed by those skilled in the art, including surface coating modification, electrolyte additive control, three-dimensional structure construction, alloying, heat treatment, and laser surface processing. Among these, laser surface processing technology offers advantages such as simple processing, no need to introduce additional chemical reagents, high spatial resolution, high processing efficiency, and applicability to large-area fabrication. It can directly construct micro- and nano-structures on the metal surface, thereby regulating interfacial wettability, electric field distribution, and ion transport behavior.

[0005] However, existing laser treatment methods for zinc anodes primarily rely on laser ablation to construct regular structures on the zinc foil surface through material removal, such as grooves, stripes, holes, lattices, or microchannels, to increase the electrode's specific surface area or improve ion transport pathways. While these methods can improve zinc deposition behavior to some extent, the regular structures formed by laser ablation typically have sharp edges, abrupt depth changes, or localized high curvature regions. This not only fails to effectively homogenize the interfacial electric field distribution but also introduces new electric field concentration points at the microstructure edges, causing zinc to preferentially deposit at these edges. Furthermore, excessively high laser energy input can lead to over-ablation of the zinc foil surface, particle accumulation, crack formation, and substrate damage, thereby reducing the long-term stability of the electrode.

[0006] In summary, there is an urgent need to develop a new zinc anode surface control technology that can fully utilize the nanosecond laser-induced thermal reconstruction effect to achieve the controllable construction of zinc metal surface structure without introducing additional coatings or chemical modifications, thereby obtaining a functionalized zinc anode with continuity, stability, and interface control capabilities. Summary of the Invention

[0007] To address the problems in existing technologies where the interface control of zinc anodes mainly relies on ablation, but the edges of regular structures are prone to introducing new electric field concentration points, and excessively high laser energy can easily lead to excessive ablation of the zinc foil surface, particle accumulation, crack formation, and substrate damage, resulting in insufficient long-term electrode stability, this invention provides a nanosecond laser thermally reconstructed fish-scale zinc anode, its preparation method, and its application.

[0008] This invention is achieved using the following technical solution: This invention provides a method for preparing a nanosecond laser thermally reconstructed fish-scale-shaped zinc anode, comprising the following steps: S1, the zinc metal substrate material is one or more of zinc metal foil, sheet, plate, mesh or composite substrate material containing zinc metal layer. After cutting and flattening the zinc metal substrate material, surface contaminants and surface oxide layer are removed, and it is cleaned and dried to serve as a pretreated zinc metal substrate for later use.

[0009] S2, the pretreated zinc metal substrate is flattened and fixed on the nanosecond laser processing platform; the fixing method includes one or more of vacuum adsorption, mechanical clamping, flat pressing and fixing, and back plate support fixing, so as to reduce the structural inhomogeneity caused by material deformation or focal plane drift during the processing.

[0010] S3. A nanosecond pulsed laser is used to scan and process the surface of a zinc metal substrate. The wavelength of the nanosecond pulsed laser is 355nm~1064nm and the pulse width is 1ns~500ns. Under the action of laser thermal input, the surface of the zinc metal substrate undergoes local heating, melting, surface material migration and rapid solidification, forming a fish-scale thermal reconstruction structure.

[0011] Specifically, the processing parameters for nanosecond pulsed laser scanning are as follows: Scanning speed: 100mm / s~3000mm / s; Laser power: 5%~80% of the rated output power of the equipment; Repetition rate: 1kHz~500kHz; Line spacing: 1μm~500μm; Number of scans: 1~20.

[0012] Preferably, when the thickness of the zinc metal substrate is 50μm~200μm: the scanning speed is 700~1300mm / s; the laser power is 20%~35% of the rated output power of the equipment; and the repetition frequency is 20~50kHz.

[0013] Optimal, when the zinc metal substrate is 100μm, the scanning speed is 1000mm / s; the laser power is 30% of the rated output power of the equipment; and the repetition frequency is 30kHz.

[0014] S4 involves cooling the laser-processed zinc metal substrate, cleaning its surface (blowing, washing, and drying), and trimming its shape without introducing any external coatings or active substances. This ensures that the resulting structure primarily originates from the thermal reconstruction of the zinc metal substrate itself, resulting in a zinc anode with a fish-scale-like thermal reconstruction structure on its surface.

[0015] This invention provides a nanosecond laser thermally reconstructed fish-scale zinc anode, comprising a zinc metal substrate, the surface of which is covered with a fish-scale thermally reconstructed structure. The fish-scale thermally reconstructed structure is formed by the zinc substrate itself through nanosecond laser thermal action, resulting in localized heating, melting, surface material migration, and rapid solidification on the zinc metal surface. It includes several continuously distributed and overlapping arc-shaped scale-like recessed units, unlike the straight grooves, hole arrays, regular dot lattices, or mechanical imprint structures formed by traditional laser etching. It does not contain any external coatings, deposition layers, or mechanical imprint structures. Each recessed unit has a smooth edge structure, which can be used to improve the ion transport and deposition behavior at the zinc anode interface.

[0016] This invention provides an application of a nanosecond laser thermally reconfigured fish-scale zinc anode, used in the anode of an aqueous zinc-ion battery. The aqueous zinc-ion battery includes a positive electrode, a negative electrode, a separator, and an aqueous electrolyte. The fish-scale zinc anode can improve the Zn... 2+ The transmission path and local electric field distribution make Zn 2+ It tends to nucleate and deposit uniformly within the scale structure and in the arc-shaped concave regions. Specifically, the aqueous electrolyte includes one or more aqueous solutions of ZnSO4, Zn(CF3SO3)2, Zn(CH3COO)2, ZnCl2, and Zn(TFSI)2; the positive electrode of the aqueous zinc-ion battery includes one or more of manganese-based oxides, vanadium-based oxides, Prussian blue-based materials, organic positive electrode materials, and carbon-based positive electrode materials.

[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a nanosecond laser thermally reconstructed fish-scale zinc anode, its preparation method, and its application. The method utilizes a nanosecond laser to scan and process the surface of a zinc metal substrate. Through localized thermal action, the zinc substrate surface undergoes sequential localized heating, melting, surface material migration, and rapid solidification, constructing a fish-scale thermally reconstructed structure with continuous arc-shaped overlaps. This fish-scale thermally reconstructed structure features smooth edges and continuous spatial distribution, reducing localized electric field concentration caused by sharp structures, thereby improving the uniformity of the zinc anode interface structure and zinc deposition / stripping behavior.

[0018] This invention directly utilizes the zinc metal substrate itself to form a stable structure through thermal reconstruction under the action of nanosecond laser, without the need to introduce additional external functional materials such as inorganic coatings, organic coatings, carbon material layers, and metal oxide layers. The preparation process is simple, requires no complex chemical treatment, and has the advantages of short process flow, environmental friendliness, and suitability for large-area processing.

[0019] This invention provides a continuously distributed microscale deposition space by constructing a fish-scale-like thermal remodeling structure, and improves Zn deposition by utilizing the confinement effect between the arc-shaped concave regions and the scale units. 2+ Transport and local deposition environment guide Zn 2+ Nucleation and growth occur in relatively uniform locations, reducing localized protruding growth and thus improving the uniformity of the zinc deposition / stripping process.

[0020] This invention also utilizes the thermal regulation effect during the nanosecond laser thermal reconstruction process to simultaneously repair local defects on the zinc surface, smooth sharp protrusions, and adjust the surface microstructure, thereby reducing interfacial instability caused by original rolling defects and uneven surface areas, and further improving the structural stability of the zinc anode during long-term cycling.

[0021] The nanosecond laser processing method used in this invention has good parameter adjustability. By adjusting parameters such as laser scanning speed, laser power, repetition frequency, line spacing, defocusing amount, and number of scans, the size, continuity, coverage, and degree of thermal reconstruction of the fish-scale thermal reconstruction structure can be controlled, thus making it suitable for zinc substrates of different thicknesses and different aqueous zinc-ion battery systems.

[0022] When the fish-scale-shaped thermally reconstructed zinc anode prepared by this invention is applied to aqueous zinc-ion batteries, it exhibits lower deposition / stripping polarization, more stable zinc deposition behavior, higher rate adaptability, and longer cycle life, which is beneficial to improving the overall electrochemical performance of aqueous zinc-ion batteries. Attached Figure Description

[0023] Figure 1This is a schematic diagram comparing the surface morphology of untreated zinc foil and zinc foil treated with nanosecond laser. The left side is untreated zinc foil, and the right side is zinc foil treated with nanosecond laser.

[0024] Figure 2 This is a schematic diagram of the surface morphology evolution of zinc foil under different nanosecond laser parameters. From left to right, it shows the mildly modified region, the fish-scale thermal reconstruction region, and the excessively ablated region.

[0025] Figure 3 This is a scanning electron microscope image of Comparative Example 1.

[0026] Figure 4 This is a scanning electron microscope image of Comparative Example 2.

[0027] Figure 5 This is a scanning electron microscope image of Example 1.

[0028] Figure 6 This is a scanning electron microscope image of Comparative Example 3.

[0029] Figure 7 This is a comparison chart of the cycle performance of a symmetrical battery assembled with an untreated zinc anode and the fish-scale zinc anode of this invention.

[0030] Figure 8 Rate performance of the untreated zinc anode and the fish-scale zinc anode of the present invention.

[0031] Figure 9 The graph shows a comparison of the Zn||Cu coulombic efficiency between the untreated zinc anode and the fish-scale zinc anode of this invention. Detailed Implementation

[0032] The specific embodiments of the present invention will be described in detail below. Example 1

[0033] A nanosecond laser thermally reconfigured fish-scale-shaped zinc anode, such as Figure 1 As shown, it includes the following steps: S1. A commercial zinc foil with a thickness of 100μm was selected as the zinc metal substrate. It was cut into 4cm×4cm pieces, flattened, and then the surface of the zinc foil was cleaned alternately with ethanol and deionized water to remove surface oil, dust and loose surface oxides. It was then dried and set aside as a pretreated zinc metal substrate.

[0034] S2, the pretreated zinc metal substrate is flattened and fixed on the nanosecond laser processing platform.

[0035] S3 uses a nanosecond pulsed laser to scan and process the surface of a zinc metal substrate. The scanning speed is 1000 mm / s, the laser power is 30% of the rated output power of the equipment, and the repetition frequency is 30 kHz.

[0036] Under the transient thermal action of nanosecond laser, the surface of the zinc metal substrate undergoes local heating, melting, surface material migration and rapid solidification, forming a continuous fish-scale thermal reconstruction structure on the zinc substrate surface.

[0037] S4 involves cooling the laser-processed zinc metal substrate, cleaning its surface (blowing, washing, and drying), and trimming its shape without introducing any external coatings or active substances. This ensures that the resulting structure is primarily derived from the thermal reconstruction of the zinc metal substrate itself, resulting in a zinc anode with a fish-scale-like thermal reconstruction structure on its surface. The resulting sample is denoted as ns-SL-Zn. Comparative Example 1

[0038] Commercial zinc foil that has not undergone nanosecond laser treatment was used as Comparative Example 1 and was used to fabricate the zinc anode.

[0039] Due to defects such as rolling marks, scratches, grain boundaries, and local protrusions on the surface, Zn is easily generated during cycling. 2+ Uneven flux leads to dendrite growth and side reactions.

[0040] like Figure 1 As shown, compared with the untreated zinc foil of Comparative Example 1, the zinc foil surface of Example 1 after nanosecond laser treatment forms obvious continuous microstructure regions. Comparative Example 2

[0041] Laser parameters lower than the effective thermal reconstruction window are used for processing.

[0042] Due to insufficient heat input, the zinc surface cannot form a continuous fish-scale structure, resulting only in slight roughening, which cannot effectively improve the zinc deposition behavior. Comparative Example 3

[0043] Laser parameters higher than the effective thermal reconstruction window are used for processing.

[0044] Due to excessive energy input, the zinc surface exhibits phenomena such as excessive ablation, particle accumulation, porosity, and cracks, leading to a decrease in interface stability. Example 2

[0045] A nanosecond laser thermally reconstructed fish-scale-shaped zinc anode was developed to study the effect of nanosecond laser energy input on the surface structure evolution of zinc foil. Except for the scanning speed, laser power, and repetition frequency in step S3, the rest were completely consistent with Example 1. Specifically, the scanning speeds were set to 700, 850, 1000, 1150, and 1300 mm / s, respectively; the laser power was set to 0%, 25%, 30%, and 35% of the rated output power of the equipment; and the repetition frequency was set to 20, 30, 40, and 50 kHz.

[0046] Zinc foil surface structure modulation under different nanosecond laser parameters: Depend on Figure 2 It can be seen that as the nanosecond laser energy input changes, the surface of the zinc metal substrate exhibits different degrees of structural evolution characteristics.

[0047] When the laser energy input is low, only a slight thermal effect occurs on the surface of the zinc metal substrate, forming a slightly modified surface region, which cannot effectively construct a continuous microstructure. When the laser energy is within a suitable range, the zinc surface undergoes sufficient melting and rapid resolidification, forming a continuous, smooth, and overlapping fish-scale-like thermally reconstructed microstructure, which is the target structure of this invention. When the laser energy is further increased, excessive melting and material removal occur on the zinc surface, resulting in excessive ablation phenomena such as particle accumulation, pores, and cracks, which is detrimental to interface stability.

[0048] The formation of fish-scale thermally reconstructed structures depends on a suitable nanosecond laser thermal input window. Only within the parameter range can continuous, uniform fish-scale thermally reconstructed microstructures with excellent interface control be obtained.

[0049] Structural characterization: The surface morphology of the ns-SL-Zn obtained in Example 2 was observed using a scanning electron microscope.

[0050] like Figure 3 As shown, the untreated zinc foil surface exhibits obvious rolling textures and localized irregular defects; such as Figure 4 As shown, the sample surface treated with light laser only showed limited roughening and failed to form a continuous microstructure; as Figure 5 As shown, under optimized laser parameters, a continuous fish-scale-like thermal reconstruction structure is formed on the surface. The scale units overlap and are evenly distributed, with smooth edges. Figure 6 As shown, when the laser energy is too high, obvious particle accumulation and excessive ablation occur on the surface, and the structural integrity is damaged.

[0051] Further analysis was conducted on the formation mechanism of the nanosecond laser-induced fish-scale structure. During the nanosecond laser treatment, the zinc surface successively undergoes stages of local heating, melting, surface material migration, and rapid solidification, ultimately forming a fish-scale thermally remodeled structure. Since this structure originates from the thermal remodeling process of the zinc substrate itself, there are no additional deposited layers or coatings on the surface, and the intrinsic properties of the zinc substrate are preserved.

[0052] Regulatory effect on zinc deposition behavior: To analyze the influence of fish-scale thermally remodeled microstructure on zinc deposition behavior, an evolution model of the interface between the untreated zinc anode and the ns-SL-Zn anode was established.

[0053] For Comparative Example 1, due to the presence of rolling grooves, scratches, and local protrusions on the surface, localized areas of enhanced electric field are easily generated during the deposition process, making Zn... 2+ Preferential deposition in defect areas, and further induce tip growth.

[0054] In Example 1, the arc-shaped recessed regions in the fish-scale structure provide a continuous deposition space, while the smooth edges of the structure reduce local electric field concentration, allowing Zn to... 2+ It can nucleate and grow more evenly.

[0055] During long-term deposition / exfoliation, the fish-scale thermal remodeling structure can maintain a more stable interface evolution process, reducing uneven deposition, dendrite growth, and by-product accumulation.

[0056] Cycle performance test of aqueous zinc symmetric battery: The ns-SL-Zn obtained in Example 1 was used as the negative electrode to assemble a Zn||Zn symmetric cell, and untreated commercial zinc foil was used as a comparative example.

[0057] The battery adopts the CR2032 button cell structure, the separator is a glass fiber separator, and the electrolyte is a 2mol / L ZnSO4 aqueous solution.

[0058] like Figure 7 As shown, at a current density of 1 mA cm⁻¹ -2 Surface capacity is 1mAh cm -2 Under the given conditions, the symmetric cell of Example 1 exhibited a stable deposition / stripping process.

[0059] Further at 5mA cm -2 and 1mAh cm -2 Tested under the following conditions.

[0060] The results show that ns-SL-Zn can maintain a relatively stable voltage response, while untreated zinc foil shows a significant increase in polarization and voltage fluctuations.

[0061] Under specific test conditions: Example 1 at 1mA cm -2 Stable cycling for over 2000 hours; at 5mA cm -2 The electrode remained stable for over 3500 hours under normal cycling conditions. This indicates that the fish-scale thermal remodeling structure can effectively improve the long-term cycling stability of the zinc anode.

[0062] Rate performance and zinc deposition / stripping reversibility testing: Zn||Zn symmetric cells were assembled in Example 1 and Comparative Example 1, respectively. The test current densities were set sequentially to 1, 2, 5, 10, and 15 mA cm⁻¹. -2 .like Figure 8As shown, Example 1 maintains a relatively stable voltage response as the current density increases, and returns to stable cycling after the current density is restored.

[0063] The coulombic efficiency of zinc deposition / stripping was further tested using a Zn||Cu half-cell. Figure 9 As shown, compared to Comparative Example 1, Example 1 exhibits a more stable coulombic efficiency change, indicating that it has superior zinc deposition / stripping reversibility.

[0064] The scope of protection claimed by this invention is not limited to the specific embodiments described above. Moreover, for those skilled in the art, this invention can have various modifications and alterations. Any modifications, improvements, and equivalent substitutions made within the concept and principles of this invention should be included within the scope of protection of this invention.

Claims

1. A method for preparing a nanosecond laser thermally reconstructed fish-scale-shaped zinc anode, characterized in that, Includes the following steps: S1. After cutting and flattening the zinc metal substrate material, remove surface contaminants and surface oxide layer, clean and dry it to prepare it as a pretreated zinc metal substrate for later use. The zinc metal substrate material is one or more of zinc metal foil, sheet, plate, mesh or composite substrate material containing zinc metal layer. S2, the pretreated zinc metal substrate is flattened and fixed on the nanosecond laser processing platform; S3, a nanosecond pulsed laser is used to scan and process the surface of a zinc metal substrate. The wavelength of the nanosecond pulsed laser is 355nm~1064nm and the pulse width is 1ns~500ns. Under the action of laser thermal input, the surface of the zinc metal substrate undergoes local heating, melting, surface material migration and rapid solidification, forming a fish-scale thermal reconstruction structure. S4 involves cooling, cleaning, and shaping the laser-processed zinc metal substrate to obtain a zinc anode with a fish-scale thermal reconstruction structure on its surface.

2. The method for preparing a nanosecond laser thermally reconstructed fish-scale-shaped zinc anode according to claim 1, characterized in that, In step S2, the fixing method includes one or more of the following: vacuum adsorption, mechanical clamping, flat pressing and fixing, and back plate support fixing.

3. The method for preparing a nanosecond laser thermally reconstructed fish-scale-shaped zinc anode according to claim 1, characterized in that, In step S3, the processing parameters for nanosecond pulsed laser scanning are as follows: Scanning speed: 100mm / s~3000mm / s; Laser power: 5%~80% of the rated output power of the equipment; Repetition rate: 1kHz~500kHz; Line spacing: 1μm~500μm; Number of scans: 1~20.

4. The method for preparing a nanosecond laser thermally reconstructed fish-scale-shaped zinc anode according to claim 3, characterized in that, When the thickness of the zinc metal substrate is 50μm~200μm: the scanning speed is 700~1300mm / s; the laser power is 20%~35% of the rated output power of the equipment; and the repetition frequency is 20~50kHz.

5. A nanosecond laser thermally reconfigured fish-scale-shaped zinc anode prepared according to the method described in claim 1, characterized in that, The invention includes a zinc metal substrate, the surface of which is covered with a fish-scale thermal reconstruction structure. The fish-scale thermal reconstruction structure is formed by the zinc substrate itself through nanosecond laser thermal action and includes several continuously distributed and overlapping arc-shaped scale-like recessed units, each recessed unit having a smooth edge structure.

6. The application of the nanosecond laser thermally reconfigured fish-scale zinc anode according to claim 5, characterized in that, It is used in the negative electrode of an aqueous zinc-ion battery, which includes a positive electrode, a negative electrode, a separator, and an aqueous electrolyte.

7. The application of the nanosecond laser thermally reconfigured fish-scale zinc anode according to claim 6, characterized in that, The aqueous electrolyte includes one or more aqueous solutions of ZnSO4, Zn(CF3SO3)2, Zn(CH3COO)2, ZnCl2, and Zn(TFSI)2.

8. The application of the nanosecond laser thermally reconfigured fish-scale zinc anode according to claim 6, characterized in that, The positive electrode of the aqueous zinc-ion battery includes one or more of the following: manganese-based oxide, vanadium-based oxide, Prussian blue-based materials, organic positive electrode materials, and carbon-based positive electrode materials.